Expression and Purification of Human Keratinocyte Growth Factor 2 by Fusion with SUMO - Wu, Xiaoping (Mol Biotechnol, 2008)
Small ubiquitin-related modifier (SUMO) fusion system has been shown to be efficient for enhancing expression and preventing degradation of the target protein. We showed herein that SUMO fusion to human keratinocyte growth factor 2 (hKGF-2) gene was feasible and it significantly enhanced protein expression and its efficiency. The fusion DNA fragment composed of SUMO gene, which was fused to hexahistidine tag, and hKGF-2 gene was amplified by PCR and inserted into the expression vector pET28a to construct the recombinant plasmid, pET28a-SUMO-hKGF-2. The plasmid was then transformed into Escherichia coli Rosetta(TM)2(DE3), and the recombinant fusion protein SUMO-hKGF-2 was expressed at 30°C for 6 h, with the induction of IPTG at the final concentration of 0.4 mM. The expression level of the fusion protein was up to 30% of the total cellular protein. The fusion protein was purified by Ni-NTA affinity chromatography. After desalting by Sephadex G-25 size exclusion chromatography, the hexahistidine-SUMO-hKGF-2 was digested by SUMO proteases. The recombinant hKGF-2 was purified again with Ni-NTA column and the purity was about 95% with a total yield of 13.9 mg/l culture. The result of mitogenicity assay suggests that the recombinant hKGF-2 can significantly promote the proliferation of normal rat kidney epithelial (NRK-52E) cells.